"u = x+y+z,v=x^2+y^2-z^2. \\ F(u,v)=0.\n\\newline\n0 = F_x = \\frac{\\partial F}{\\partial u}\\frac{\\partial u}{\\partial x}+\\frac{\\partial F}{\\partial v}\\frac{\\partial v}{\\partial x}.\n\\newline\n0 = F_y = \\frac{\\partial F}{\\partial u}\\frac{\\partial u}{\\partial y}+\\frac{\\partial F}{\\partial v}\\frac{\\partial v}{\\partial y}.\n\\newline\nLet \\ \\frac{\\partial u}{\\partial x}=\\frac{\\partial u}{\\partial x}\\frac{\\partial x}{\\partial x} + \\frac{\\partial u}{\\partial y}\\frac{\\partial y}{\\partial x}+\\frac{\\partial u}{\\partial z}\\frac{\\partial z}{\\partial x}=1+p.\n\\newline\nLet \\ \\frac{\\partial u}{\\partial y}=\\frac{\\partial u}{\\partial x}\\frac{\\partial x}{\\partial y} + \\frac{\\partial u}{\\partial y}\\frac{\\partial y}{\\partial y}+\\frac{\\partial u}{\\partial z}\\frac{\\partial z}{\\partial y}=1+q.\n\\newline\n\\frac{\\partial v}{\\partial x}=2x-2zp.\n\\newline\n\\frac{\\partial v}{\\partial y}=2y-2zq.\n\\newline\nF_x=\\frac{\\partial F}{\\partial u}(1+p)+\\frac{\\partial F}{\\partial v}(2x-2pz)=0.\n\\newline\nF_y=\\frac{\\partial F}{\\partial u}(1+q)+\\frac{\\partial F}{\\partial u}(2y-2qz)=0.\n\\newline\nEliminating \\ \\frac{\\partial F}{\\partial u} and \\frac{\\partial F}{\\partial v} we \\ get:\n\\newline\n(1+p)(2y-2qz)-(1+q)(2x-2pz)=0.\n\\newline\ny-qz+yp-qpz-x+pz-qx+qpz=0.\n\\newline\np(y+z)-q(x+z)=x-y \\ - the \\ resulting \\ equation."
Comments
Leave a comment